Parasitoid phorid flies (Diptera: Phoridae) from the threatened leafcutter ant Atta robusta Borgmeier (Hymenoptera: Formicidae) - Brown, Brian V.; Braganca, Marcos A. L.; Gomes, Diego S.; Queiros, Jarbas M.; Teixeira, Marcos C. (Zootaxa, 2012)
Phorid flies are well known natural enemies of leafcutter ants, but there is no information on phorid species associatedwith the threatened species Atta robusta Borgmeier. During 2009 and 2010 we collected phorid parasitoids of A. robustaat Guriri Island, Espirito Santo (18o43’S; 39o 45’W) and at Rio de Janeiro city (23°01’S; 43°28’W). Three new specieswere found: Eibesfeldtphora breviloba Brown, E. digitata Brown, and Myrmosicarius exrobusta Brown. These species,the attack behavior of the two species of Eibesfeldtphora, as well as the anti-parasitoid defense behavior of A. robusta, are described.